Kampanye Digital Activism untuk Mendorong Rekayasa Sosial Kebersihan Lingkungan di Instagram @Pandawaragroup - Devani Oktavianti; Andi Windah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Research with the title "Digital Activism Campaign to Encourage Social Engineering for Environmental Hygiene (Case Study on the Instagram Social Media Account @PandawaraGroup)", this research aims to find out how the movement to educate people to care more about the environment initiated by the Pandawara Group can create a waste-free environment by Cleaning up trash has become a form of digital activism in a networked society. This research analysis uses the critical discourse analysis method with a social change approach. Environmental cleanliness is one of the main factors for the survival of life with a clean environment with fresh air. The waste clean-up action carried out by the Pandawara Group started out of concern about seeing floods that often hit their home area. Therefore, Pandawara Group hopes that the action they take can raise public awareness not to litter.